2022
DOI: 10.1021/acs.est.2c04101
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Quantification of Particle-Bound Criegee Intermediates in Secondary Organic Aerosol

Abstract: The ozonolysis of alkenes contributes substantially to the formation of secondary organic aerosol (SOA), which are important modulators of air quality and the Earth’s climate. Criegee intermediates (CIs) are abundantly formed through this reaction. However, their contributions to aerosol particle chemistry remain highly uncertain. In this work, we present the first application of a novel methodology, using spin traps, which simultaneously quantifies CIs produced from the ozonolysis of volatile organic compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…These organic compounds are likely to have a relatively low volatility since they are already present in the film, and therefore it is quite likely that the secondary ozonide and hydroperoxide products will also be of low volatility. 87 Carboxylic acids are present at high concentrations in skin oil and will react with Criegee intermediates forming α-acyloxy hydroperoxides. 88–90 Palmitic acid is the most common fatty acid in human skin and is likely to react with Criegee intermediates formed by squalene ozonolysis, leading to a variety of products such as those listed in Table S1 † 88,90 .…”
Section: Discussionmentioning
confidence: 99%
“…These organic compounds are likely to have a relatively low volatility since they are already present in the film, and therefore it is quite likely that the secondary ozonide and hydroperoxide products will also be of low volatility. 87 Carboxylic acids are present at high concentrations in skin oil and will react with Criegee intermediates forming α-acyloxy hydroperoxides. 88–90 Palmitic acid is the most common fatty acid in human skin and is likely to react with Criegee intermediates formed by squalene ozonolysis, leading to a variety of products such as those listed in Table S1 † 88,90 .…”
Section: Discussionmentioning
confidence: 99%
“…As this is several orders of magnitude smaller than the combined CI loss rate (second term of Eq ), thought to be on the order of 10 2 s –1 , the CIs are expected to reach their maximum concentration rapidly. Recent experimental evidence has indicated that CIs remain detectable for minutes after their formation in viscous secondary organic aerosol, longer than the 39 s flow tube residence time in this work, suggesting that the CI population may not deviate far from a steady-state concentration over the duration of the measurements reported here. In addition, as discussed in Section , the results of this simple kinetic model agree with explicit kinetic simulations where no such steady-state assumptions are made.…”
Section: Discussionmentioning
confidence: 53%
“…Given its extremely rapid reaction with Fe­(II), however, it seems likely that it should be consumed as soon as it is absorbed. Highly viscous aerosol particles can potentially stabilize reactive species, , and thus, the concentration of PAA or other organic peracids present in an aerosol may be higher immediately after the particle dissolves upon activation to become a cloud droplet. While not yet investigated, it is also possible that the “burst” chemistry takes place in particles when they deliquesce.…”
Section: Resultsmentioning
confidence: 99%
“…Organic peracids have been detected in biogenic and anthropogenic SOA; they are multigeneration oxidation products in ambient SOA, formed when volatile organic compounds are oxidized by OH or O 3 . While they are relatively reactive, reactive species have been shown to be preserved in viscous SOA particles . This could preserve substantial concentrations of peracids, which upon interaction with a cloud droplet, liberate peracids upon dissolution, which in the presence of Fe­(II) (which has a typical concentration of 10 –7 – 10 –4 M in ambient cloudwater) represents an additional large source of OH in cloudwater .…”
Section: Atmospheric and Environmental Implicationsmentioning
confidence: 99%
See 1 more Smart Citation